EDUKASI BAHAYA MODUS KEJAHATAN SOCIAL ENGINEERING - Krey, Thresia Hilda M.Y.; Senandi, Winna A.A. (JURNAL PENGABDIAN PAPUA, 2024)
Social engineering is a cyber crime that involves the perpetrator using an individual's mistake or carelessness to steal important confidential data or information such as personal information, passwords, financial data, or accessing a computer system in an unauthorized way. Perpetrators usually use psychological tricks so they can easily trick other people and make others unaware even through communication tools because the perpetrators take advantage of someone's reaction when planning their attack. This outreach activity with the title "Education on the Dangers of Social Engineering Crime Modes" was carried out at Abepura Adventist Elementary and Middle School with the target participants being school children and teenagers. This outreach activity is carried out with the target of school children to provide an understanding of the dangers of the social engineering crime mode and the various actions that need to be taken so that we avoid the social engineering crime mode, as well as legal steps that can be taken if we are caught in the social engineering crime mode. During the activity, the enthusiasm of the participants was visible, especially when providing responses during the question and answer session at the end of the activity. It is hoped that this activity will be useful for the participants so that they can act as a relay for other communities to spread and understand the dangers of the social engineering information crime mode, and also as an indirectly useful effort to protect the people in Jayapura City. Keywords: cybercrime; cyberspace; social engineering; social media; ITE law